Factors Affecting Social Accountability in Service Providing Public Sectors: Exploring Beneficiaries’ Perspectives in Jimma Zone (Research, Society and Development, 2019)
This study was undertaken to identify the factors affecting social accountability in service providing public sector organizations from beneficiary perspectives in Jimma Zone. Factors hindering social accountability, social accountability mechanisms implemented in public sectors and the role of social accountability were the objectives assessed in this study. Qualitative research approach was employed. Beneficiaries of four public sectors (health, education, agriculture and water) were selected purposively because these are the main focus of the Ethiopian Social Accountability Program (ESAP2). Two administrative towns (Jimma and Agaro) and two woreda/kebele towns (Limu Kosa and Gera districts) were purposively selected for this study. Eight Focus group discussion, sixteen in-depth interviews and four key informant interviews were conducted.  The main findings of the study revealed that factors hindering social accountability are the low citizens’ rights awareness and the socio cultural barriers that limit speaking out, absence of access to information guarantees rendering government income and expenditure because beneficiaries lack of their right awareness up to this and service provider’s unwillingness to share information. Community score cards and service providers in face to face meetings are the two commonly implemented social accountability mechanisms respectively.  Based on the findings the researchers recommended that long- term institutional reforms to make the public sectors more accountable to citizens, devolutions to local government levels or responsibility and accountability for service provision, community and civil society participation should have to be encouraged by the government.